Effects of Transitional Physical Therapy Program for Stroke Patients and Caregivers on activity of daily living and movement from hospital to home - Parnthong, Pimchanok; Hengbumrung, Gaogarnda (Hua Hin Medical Journal, 2025)
Background: It is important to recognize that stroke is a disease that has widespread impact. Many patients face mobility challenges, some encounter physical disabilities, and some face a combination of disability and mortality due to limited knowledge, practical skills, and physical rehabilitation. Objective: The purpose of this study is to investigate the effects of a physical therapy program for stroke patients and their caregivers during the transition period from hospital to home on the caregivers' knowledge and skills, the patients' mobility and ability to perform activities of daily living. Method: This study is an experimental research design (Randomized Controlled Trials; RCT) with two groups: an experimental group and a control group, each consisting of 46 participants. Each group includes 23 stroke patients and 23 caregivers. The experimental group receives a physical therapy program for both stroke patients and their caregivers during the hospital-to-home transition, while the control group receives traditional physical therapy. Data is collected by comparing the caregivers' knowledge and skills, as well as evaluating patients' mobility tested by the STREAM information scale and ability to perform activities of daily living tested by Barthel Index scale. The data is then analyzed using independent t-tests. Results: It was found that the caregivers’ skills, activities of daily living (Barthel Index) and patients' mobility (STREAM) between the control and experimental groups increased and were significantly different at the 0.05 statistical level. The difference in scores was 11.6 (5.7, 17.5), 13.3 (7.1, 19.4), and 11.3 (6.0, 16.7) respectively. However, the caregivers' knowledge scores did not differ significantly between the two groups. Conclusion: The physical therapy program for stroke patients and their caregivers during the hospital-to-home transition can enhance caregivers' skills, as well as improve patients' ability to perform daily activities and their mobility.